Pengaruh Pemberian Gel Teripang Emas Terhadap Jumlah Osteoklas Di Daerah Tekanan Pada Remodeling Tulang Pergerakan Gigi Ortodonti - Stefany Wijaya; Noengki Prameswari; Maria Lisdiana T (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Orthodontic treatment takes a long time for bone remodeling. Stichopus hermanii has various compounds such as EPA-DHA, calcium, magnesium, f lavonoid and triterpenoid, that may reduce the number of osteoclasts. Research Stichopus hermanii against osteoclasts in bone remodeling has not been investigated. Purpose: This study aimed to verify the effect of Stichopus hermanii gel to the number of osteoclasts in bone remodeling pressure area of orthodontic, tooth movement. Materials and Methods: Forty-eight male Cavia cobaya were divided into eight groups. (K1) and (K3) negative control for 6 and 14 days. (K2) and (K4) positive control for 6 and 14 days by provision of separator and NaCMC gel. (P1), (P3) and (P2), (P4) were treated for 6 and 14 days by provision of separator and Stichopus hermanii gel 3% and 3.5%. Osteoclasts were examited calculated by histological preparations with HE staining and viewed using a light microscope with 400x magnification, and then analyzed by ANOVA followed by LSD test. Result: In analysis descriptive the mean of K1, K2, K3, K4, P1, P2, P3, and P4 are (3,33 ± 1,211), (10,67 ± 1,211), (8,33 ± 0,816), (4,33 ± 1,211), (3 ± 0,894), (14,3 ± 1,633), (9,33 ± 1,366), and (12,67 ± 2,338) ANOVA showed a significant difference in the number of osteoclasts. LSD test showed significant differences in the number of osteoclasts in all groups. Conclusion: Stichopus hermanii gel with a concentration of 3,5% more effective on day 6, and the concentration of Stichopus hermanii gel 3% is more effective on the 14th day by reducing the number of osteoclasts in bone remodeling pressure area orthodontic tooth movement.